Propulsion System Design For The Indonesian Semi High Speed Train - Lukman Shalahuddin; Kartiko E. Putranto; Dimas B. Eskayudha (Majalah Ilmiah Pengkajian Industri, 2020)
This paper describes a study on the development of methodology to select the most appropriate technology, and the most optimum design and configuration for the propulsion system of the semi-high speed intercity train that will be operated on the Jakarta-Surabaya corridor. It also describes the method to calculate resistance loads Â and tractive forces and hence the power required to propel the train along the specified route within targeted time. Among the output of this study is a recommendation for the most optimum propulsion system with basic/ main parameters for main components such as diesel engine, traction motor and the possibility of Diesel Electric Multiple Unit (DEMU) Hybrid battery system.